2002
DOI: 10.1074/jbc.m109958200
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor α Increases the Expression of Glycosyltransferases and Sulfotransferases Responsible for the Biosynthesis of Sialylated and/or Sulfated Lewis x Epitopes in the Human Bronchial Mucosa

Abstract: There is increasing evidence that inflammation may affect glycosylation and sulfation of various glycoproteins. The present study reports the effect of tumor necrosis factor ␣ (TNF-␣), a proinflammatory cytokine, on the glycosyl-and sulfotransferases of the human bronchial mucosa responsible for the biosynthesis of Lewis x epitope and of its sialylated and/or sulfated derivatives, which are expressed in human bronchial mucins. Fragments of macroscopically normal human bronchial mucosa were exposed to TNF-␣ at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
90
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 76 publications
8
90
0
1
Order By: Relevance
“…43,44 Studies have shown a role for sialic acid and sugars present on mucosal surfaces as receptors for microorganisms. 9 We find a significant increase in sialic acid, fucose, hexose, and hexosamine in surfactant and BBM in rats only at 3 months after initiation of CCl 4 treatment, which continued to increase until 5 months. These changes could be the result of the oxidative stress, because free radicals can modulate the activity of glycosyltransferase or glycosidases, which might in turn alter glycosylation pattern.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…43,44 Studies have shown a role for sialic acid and sugars present on mucosal surfaces as receptors for microorganisms. 9 We find a significant increase in sialic acid, fucose, hexose, and hexosamine in surfactant and BBM in rats only at 3 months after initiation of CCl 4 treatment, which continued to increase until 5 months. These changes could be the result of the oxidative stress, because free radicals can modulate the activity of glycosyltransferase or glycosidases, which might in turn alter glycosylation pattern.…”
Section: Discussionmentioning
confidence: 87%
“…8 Changes in glycosylation on the surface of intestinal epithelial cells can thus lead to increased bacterial adherence. Reactive oxygen species can modulate glycosylation on the cell surface 9 and also alter the surface viscosity of the mucus, 10 both of which may facilitate bacterial binding. Earlier studies from our laboratory have shown that oxidative stress in the intestinal mucosa after surgical manipulation results in altered glycosylation of the mucosal membranes and bacterial adherence.…”
mentioning
confidence: 99%
“…TNF-α has been shown to stimulate increased expression of several sialyl-, fucosyl-, and sulfotransferases (19). We evaluated the mRNA expression of TNF-α in MKN45 cells infected with Tx30a and 26695 strains and observed that TNF-α was barely detectable in uninfected cells.…”
Section: Figurementioning
confidence: 99%
“…Lewis antigens are particularly important in kidney transplants because rejection is lower in transplants involving Lewis-compatible donors and receptors (Oriol et al, 1978;Williams et al, 1978;Oriol and Danilovics, 1980;Myser et al, 1985;Blajchman et al, 1985;Delmotte et al, 2002), and the molecular test described in this paper may be helpful in avoiding the false negative results sometimes observed whit the serological methods available for typing Lewis antigens.…”
Section: Discussionmentioning
confidence: 99%